Responses of Karenia mikimotoi to allelochemical linoleic acid: Growth inhibition, photosynthetic damage, oxidative stress and cell apoptosis - Wang, Renjun; Wang, Chao; Liu, Xiuxia; Chen, Junfeng; Liu, Chunchen; Song, Yuhao; Ding, Ning; Gao, Peike (Frontiers in Marine Science, 2023)
Linoleic acid (LA), a potentially algae-inhibiting chemical released by macroalgae, has been shown to hinder the growth of numerous bloom-forming species. The allelopathic effects of LA (varying from 100 μg/L to 900 μg/L) on harmful microalgae K. mikimotoi were examined using population growth dynamics and physiological levels of K. mikimotoi. LA (>500 μg/L) strongly inhibited algal growth with most cells halted at the S and G2 phases and an evident drop in photosynthetic pigments (chlorophyll a (chl a), chlorophyll c (chl c) and carotenoids). Furthermore, chlorophyll fluorescence parameters such as Fv/Fm, PI, ETo/RC showed a declining trend whereas ABS/RC, DIo/RC, TRo/RC showed an increasing trend with increasing LA exposure concentrations. The level of intracellular reactive oxygen species (ROS) was considerably higher, indicating that LA promoted oxidative stress in K. mikimotoi. Excessive ROS promoted apoptosis in K. mikimotoi, which was noted by increased activity of caspase-3, caspase-9, and flow cytometry (FCM) data. Furthermore, N-acetylcysteine (NAC) and N-Acetyl-Asp-Glu-Val-Asp-CHO (Ac-DEVD-CHO) lowered the apoptotic rates of the LA-treated algal cells, indicating that the aforementioned inhibitors delayed K. mikimotoi apoptosis under LA treatment. To summarize, cell cycle arrest of K. mikimotoi is less sensitive to ROS, but the overproduction of ROS generated by LA activated caspase-3 and caspase-9, which further promoted the apoptosis of K. mikimotoi. This research showed that LA might have great potential and application prospects in controlling the outbreak of harmful algae.